2014
DOI: 10.1890/es13-00281.1
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term experimental warming and nutrient additions increase productivity in tall deciduous shrub tundra

Abstract: Abstract. Warming Arctic temperatures can drive changes in vegetation structure and function directly by stimulating plant growth or indirectly by stimulating microbial decomposition of organic matter and releasing more nutrients for plant uptake and growth. The arctic biome is currently increasing in deciduous shrub cover and this increase is expected to continue with climate warming. However, little is known how current deciduous shrub communities will respond to future climate induced warming and nutrient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 57 publications
8
55
1
Order By: Relevance
“…Nitrogen addition had a positive effect on B. glandulosa radial growth. This result corroborates other studies that have shown that tundra shrubs can benefit from higher nutrient availability to increase their overall biomass (DeMarco, Mack, Bret‐Harte, et al., ; Parsons et al., ; Shaver & Chapin, ), cover or height (Press, Potter, Burke, Callaghan, & Lee, ). However, nitrogen addition‐induced increase in radial growth only occurred 3 years out of 5, indicating that nitrogen addition alone is not sufficient to insure radial growth increase.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nitrogen addition had a positive effect on B. glandulosa radial growth. This result corroborates other studies that have shown that tundra shrubs can benefit from higher nutrient availability to increase their overall biomass (DeMarco, Mack, Bret‐Harte, et al., ; Parsons et al., ; Shaver & Chapin, ), cover or height (Press, Potter, Burke, Callaghan, & Lee, ). However, nitrogen addition‐induced increase in radial growth only occurred 3 years out of 5, indicating that nitrogen addition alone is not sufficient to insure radial growth increase.…”
Section: Discussionsupporting
confidence: 90%
“…1.5°C (Marion et al., ). This being said, the positive effect of nitrogen addition corroborates the results of many experimental fertilisation studies on deciduous shrubs in high‐latitude ecosystems (Chapin et al., ; DeMarco, Mack, Bret‐Harte, et al., ; Gough et al., ; Zamin, Bret‐Harte, & Grogan, ). The positive response of B. glandulosa to enhance soil nitrogen availability shows that its growth is at least partially limited by nitrogen.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The increased abundance of shrubs in high-latitude regions has been studied extensively (e.g., Sturm et al, 2001b;Myers-Smith et al, 2011;DeMarco et al, 2014a), and numerous studies have identified links with factors such as snow cover (Sturm et al, 2001a;Pomeroy et al, 2006), radiation regime (Bewley et al, 2007), and nutrient cycling (Myers-Smith and Hik, 2013;DeMarco et al, 2014b). Regarding soil temperatures, the isolated assessment of shrub expansion indicates that the capture of drifting snow by shrubs increases snow depth and soil temperatures in winter, while shading decreases temperatures in summer (e.g., Sturm et al, 2001a).…”
Section: Implications For Feedback Processes With Climate Change 42mentioning
confidence: 99%
“…; DeMarco et al . ). This should result in larger differences in seedling performance between bryophyte species.…”
Section: Introductionmentioning
confidence: 97%